IDY Group Multimedia Cirebon’s Live Streaming Production Strategy - Muhammad Alfarizi; Farida Nurfalah (CONVERSE Journal Communication Science, 2026)
With the development of digital media, live streaming has become an increasingly important form of broadcasting in various public events. Service providers of live streaming are required to develop well-planned and adaptive production strategies for the situation. This study aims to analyse the live streaming production strategies applied by IDY Group Multimedia Cirebon in the pre-production, production and post-production stages. The study uses a qualitative descriptive approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The analysis is based on the theory of media production strategy, production management in media, and tactics for communication and engagement in digital media. The research results show that the IDY Group Multimedia Cirebon employs a systematic production strategy through the planning of flexible concepts, clear division of the crew’s responsibilities, the implementation of standard operating procedures (SOPs), and ongoing evaluation of post-production. These are the strategies in place to ensure broadcast quality and client satisfaction, despite the ongoing technical challenges such as network stability and on-site conditions. This study is expected to expand the discussion on digital media production strategies and serve as a practical reference for local live streaming service providers.